2011
DOI: 10.4236/ajps.2011.22028
|View full text |Cite
|
Sign up to set email alerts
|

Plant Regeneration Through Indirect Somatic Embryogenesis in Coelogyne Cristata Orchid

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 14 publications
1
11
0
2
Order By: Relevance
“…Therefore, it would be interesting to study the influence of sucrose combined with an osmotic agent such as mannitol and/or of a sequential supply of high concentration. Recently, Naing et al (2011) reported that the capacity of somatic embryogenesis observed on MS medium was extremely low as compared to that on 1/2 MS medium. However, to our best knowledge, there was no information about effect of basal medium on secondary embryogenesis so far.…”
Section: Secondary Somatic Embryogenesismentioning
confidence: 99%
“…Therefore, it would be interesting to study the influence of sucrose combined with an osmotic agent such as mannitol and/or of a sequential supply of high concentration. Recently, Naing et al (2011) reported that the capacity of somatic embryogenesis observed on MS medium was extremely low as compared to that on 1/2 MS medium. However, to our best knowledge, there was no information about effect of basal medium on secondary embryogenesis so far.…”
Section: Secondary Somatic Embryogenesismentioning
confidence: 99%
“…In vitro culture has proven as a better method for plant propagation that gives a great hope in plant cultivation especially orchid because this method can be used for orchid propagation in large quantities in a relative short of time (Naing et al, 2011). The succeed of in vitro culture depends on many factors, such as the explants selection, medium type, growth regulator, and nutrient availability.…”
Section: Introductionmentioning
confidence: 99%
“…[11], and Coelogyne cristata (Lindl.) [12] occurred on the medium that contained both auxin and cytokinin, where the auxin concentration was higher than the cytokinin. The optimum concentration of NAA in this experiment is 0.05 mg ⋅ L −1 , supposing that it is lower than the previous study on somatic embryogenesis in Vanda [5,13].…”
Section: Initiation and Proliferation Of Embryogenic Callusmentioning
confidence: 99%